278 Using a ventilator during cardiac arrest improves pCO2. Starting SYMEVECA study. (1st May 2022) - Hernández-Tejedor, A; González, NV; Corral, E; Benito, A; Vázquez, MI; Pinilla, R; Montero, SI; Torres, F; Elizondo, M
Abstract : Background: Ventilation affects the internal environment and intrathoracic pressures. Current recommendations suggest the use of mechanical ventilators in non-traumatic out-of-hospital cardiac arrest (OHCA) but their use is not widespread. We aim to compare gasometric parameters depending on the method for mechanical ventilation during OHCA. Method: Quasi-experimental study including all patients in OHCA attended by an EMS in a 9-month period with persistence of OHCA three minutes after early intubation. Two groups are established according to the mothod of ventilation during OHCA (ventilator in IPPV 500 ml x 12 rpm or resuscitation balloon). Demographic variables, initial rhythm, blood gas parameters 15 minutes after intubation or upon recovery of spontaneous circulation (ROSC) -whatever occurs first- and hospital complications were recorded. Continuous variables as mean ± standard deviation. Statistical analysis: comparisons with parametric techniques. Study approved by our ethics committee. Results: 167 PCEH were registered but 91 were excluded due to very early recovery (35) or violation of analysis protocol (56). Women 21%, age 63±19 years, shockable rhythm 31%. Groups were analyzed according to ventilation: IPPV (32) or resuscitation balloon (44). In patients with an arterial sample: pH 6.99±0.17 vs 6.99±0.16 (p=0.99); pCO2 67.9±18.8 vs 100.8±60.5 mmHg (p=0.13). With a venous sample: pH 7.01±0.17 vs 6.96±0.16 (p=0.28); pCO2 68.6±25.5 vs 86.5±25.0 mmHg (p=0.01), respectively. No direct ventilator-related complications were registered. Conclusion: Ventilation with a mechanical ventilator during OCHA improves ventilatory status compared to the use of a resuscitation balloon. The target sample size has not yet been reached. There were no direct complications. After completing the first phase, a second one will begin, comparing different ventilatory modes. Conflict of interest: None. Funding: None.